2015
DOI: 10.1155/2015/543517
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Decreases the Stroke Risk of Systemic Corticosteroid Treatment in Dermatitis: A Nationwide Population-Based Study

Abstract: Epidemiological studies have shown a strong association between dermatitis and stroke. Systemic corticosteroid, the mainstay treatment for dermatitis, could enhance the atherosclerotic process. Traditional Chinese Medicine (TCM) has been used for dermatitis to decrease the side effects of corticosteroid. However, the different stroke risk in dermatitis patients treated with systemic corticosteroid or TCM remains unclear. This study identified 235,220 dermatitis patients and same comorbidity matched subjects be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Finally, 12 articles were included in our meta-analysis. [1324] The results of the study selection process are shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 12 articles were included in our meta-analysis. [1324] The results of the study selection process are shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…During the past decade, research has suggested that AD is an allergic disease in which systemic inflammation involves more than just the skin, lots of epidemiologic observational studies have investigated the associations between AD and future stroke and/or MI. [1324] However, the results are inconsistent. Some of these researches suggested that AD may increase the risk of stroke and/or MI incidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnoses code was used from the International Classification of Diseases 9th Revision of the Clinical Modification (ICD-9-CM) in the database. Detailed description of the NHIRD was previously described [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers have found that PD is linked to an increased risk of stroke and a higher risk of stroke-related mortality [ 10 , 11 ]. However a number of studies have demonstrated that traditional Chinese medicine (TCM) [ 12 15 ], acupuncture [ 16 , 17 ], and Tai Chi [ 18 ] improve impairments associated with neurologic sequelae. Since none of the currently available treatments for PD are specifically designed to prevent stroke, this therapeutic area presents an important unmet need.…”
Section: Introductionmentioning
confidence: 99%